Сутність та складові механізму забезпечення конкурентоспроможності рекреаційної системи регіону - Черчик, Лариса Миколаївна; Мостенець, Олександр Володимирович; Cherchyk, Larysa M.; Mostenets, O. V. (Нац. акад. наук України, Ін-т регіонал. дослідж. НАН України, Ін-т екон. промисловості НАН України, Укр. асоц. регіон. наук., 2015)
У статті, на основі узагальнення існуючих підходів до трактування сутності механізму, запропоновано авторське визначення механізму забезпечення конкурентоспроможності рекреаційної системи регіону як сукупності взаємопов’язаних норм, правил, прийомів, методів та важелів впливу, які забезпечують реалізацію поставлених цілей щодо забезпечення конкурентних переваг на основі ефективного використання рекреаційного потенціалу та конкурентної стратегії. Визначено принципи формування, мету та цілі функціонування, об’єкт та суб’єкт механізму забезпечення конкурентоспроможності рекреаційної системи регіону, розглянуто змістовне наповнення цих складових. Розроблено модель зазначеного механізму як послідовність етапів, націлених на підвищення конкурентоспроможності рекреаційної системи регіону, формування та підтримку її конкурентних переваг.

The article is based on the generalization of the present approachesto defining the essence of the mechanism but it offers author’s definition of the mechanism ofregionalrecreationalsystem competitivenessimplementation asthe entity of interconnected norms,rules, methods and influence means, which provide the realization of goals in terms of providing competitive benefits based on effective use ofrecreational potential and competitive strategy. The formation of the mechanism of regionalrecreational system competitiveness implementation must be conducted based on the main principles: systematic, consistency, complementarity, balance, alternative, complexity. The aim of mechanism of regionalrecreational system competitiveness implementation functioning is the achievement of the certain level of competitiveness of the recreational system, providing the realization of competitive benefits in the economic, political, social conditions that characterize the recreational sphere of the region, state and the world depending on which market a certain recreational system is competing. The object of influence in a mechanism of regionalrecreational system competitiveness implementation is the competitive potential of the regional recreational system, the subject are the competitive benefits that determine the desired changes, as well as other outer factors, which are considered as opportunities that influence the development of recreational system in a positive way. The subjects of regulation can be legislative and executive state bodies, local government, companies authorities, businessmen, scientific institutes, educational establishments, nongovernmental organizations etc. They use certain methods of influence that make it possible to provide a certain level of competitiveness of the regional recreational system.
The essence and the components of the mechanism for ensuring the competitiveness of regional recreational system
Keywords: конкурентоспроможність; рекреаційна система регіону; механізм забезпечення конкурентоспроможності рекреаційної системи регіону; конкурентні переваги; рекреаційна сфера; recreationalsystem of the region; competitiveness; mechanism of competitivenessimplementation of regional recreational system; competitive benefits; recreational sphere